THE ROLE OF ARTISTIC SPEECH IN CREATING AN IMAGE IN THE WORKS OF AHMAD AZAM - Ma’rufat Qodirova Abdullayevna (American Journals Publishing, 2023)
The article presents the author's ideas about social life, image creation and analysis of artistic speech in the works of Ahmed Azam, a representative of the literature of the 80s and 90s. In the work of the writer in this place, artistic speech, image and figurative language characteristics are presented.
Keywords: Style, artistic speech, image, image, figurative language, irony